A common fixed point for generalized (ψ, φ)f,g - weak contractions - Abbas, M.; Parvaneh, V.; Razani, A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We extend the common fixed point theorem established by Zhang and Song in 2009 to generalized (ψ, φ)f,g weak contractions. Moreover, we give an example that illustrates the main result. Finally, some common fixed point results are obtained for mappings satisfying a contraction condition of the integral type in complete metric spaces.